2019
DOI: 10.31234/osf.io/y5wxs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Development of Intersectional Social Prototypes

Abstract: Race and gender information overlap to shape adults’ representations of social categories. This overlap can lead to the “psychological invisibility” of people whose race and gender identities are perceived to have conflicting stereotypes. The present research examines whether and when race begins to bias representations of gender across development. Using a speeded categorization task, Study 1 revealed that children were slower to categorize Black women as women, relative to White and Asian women as women and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Finally, our goal across these two studies was to examine children's status beliefs about gender and race separately (e.g., choosing Latinx stimuli for the gender condition, as children's beliefs about status for Latinx social categories appear later in development: [62]). However, in the real-world there are important intersectional processes that affect the content of individual's beliefs and attitudes [62,63]. For example, children as young as 5-years-old are less likely to view Black women (as compared to White women) as feminine [63].…”
Section: The Development Of Group-based Beliefs About Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our goal across these two studies was to examine children's status beliefs about gender and race separately (e.g., choosing Latinx stimuli for the gender condition, as children's beliefs about status for Latinx social categories appear later in development: [62]). However, in the real-world there are important intersectional processes that affect the content of individual's beliefs and attitudes [62,63]. For example, children as young as 5-years-old are less likely to view Black women (as compared to White women) as feminine [63].…”
Section: The Development Of Group-based Beliefs About Statusmentioning
confidence: 99%
“…However, in the real-world there are important intersectional processes that affect the content of individual's beliefs and attitudes [62,63]. For example, children as young as 5-years-old are less likely to view Black women (as compared to White women) as feminine [63]. Determining whether the content of children's status beliefs are affected in a similarly intersectional process will be an important area for subsequent research.…”
Section: The Development Of Group-based Beliefs About Statusmentioning
confidence: 99%
“…Johnson et al (2012) asked participants to categorize faces according to sex, and found that this categorization was facilitated when the matching sex category shared social stereotypes with the race, and impaired when stereotypes about the race and sex category were in conflict. Lei et al (2020) examined this effect in children, concluding that race begins biasing participant judgments of gender around 5 years of age. These effects demonstrate that in mature language users, race and gender are neither perceived independently, nor as distinct hierarchies.…”
Section: The Entanglement Of Gender With Other Social Effects On Lang...mentioning
confidence: 99%
“…Finally, we theorized that social prototypes are informed by history but we did not examine how history steeps into our mental representations. Children are able to develop complex intersectional prototypes as early as 5 years old (Lei et al, 2020). Our understanding of racial groups is learned early because race and racism are infused within the structure of society (Ray, 2019;Salter et al, 2018).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…. For instance, women vary considerably in race, physical features, and psychological traits, but some women (e.g., White women, stereotypically feminine women) are seen as more prototypical and representative of the female gender group than others (e.g., Black women, masculine women) in most Western societies (Goh et al, 2021;Lei et al, 2020;Purdie-Vaughns & Eibach, 2008;Thomas et al, 2014). Those that deviate from the prototypical image of their social groups are often disliked, forgotten, punished, or discredited (Goh et al, 2021;Phelan & Rudman, 2010;Purdie-Vaughns & Eibach, 2008;Schug et al, 2017;Sesko & Biernat, 2010;Vogel et al, 2021).…”
mentioning
confidence: 99%